Efektivitas dan Dampak Program Revitalisasi Pasar Tradisional di Pasar Agung Peninjoan - Pradnya Paramita, A. A. Istri Mirah; Ayuningsasi, A. A. Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2013)
Over the past view decade, consumption patterns only know traditional market as a place for find their needs. Threats to the existence of traditional market arise due to the legality of foreign ownership of the retail company and also the interest of traditional market has not accomodated yet. In addition of negative image that attached on traditional market, income's increasing is the most influential factor to the changes of purchasing power and people's lifestyles. Traditional Market Revitalization Program was initiated with the intention of solving the exist problems with physical condition's touching and market governance that will increasing the visit of the consumer so that will bring real impact on traders income. The goal of this study was for determine the the effectiveness and impact of the revitalization program of traditional markets in Pasar Agung Peninjoan. With a total sample of 78 traders from the total population of 353 with accidental sampling method. By descriptive analysis and Wilcoxon test, then obtained results show that the effectiveness of the traditional market revitalization program running quite effective with total more less 71.79 percent. This program give a significant and positive impact to the market physical condition, market governance and traders income.
Keywords: Traditional Market Revitalization Program; Physical; Market Governance; Traders Income